NOAA's National Centers for Environmental Information Space Weather Data Inventory Status - Alessandra Abe Pacini; Laurel Rachmeler; Kimberly Baugh (Space Weather, 2025)
Abstract We present here an updated overview of the Space Weather data curated and/or generated, improved, archived, and disseminated by the Solar Terrestrial Physics (STP) Section of the National Centers for Environmental Information (NCEI) in the National Oceanic and Atmospheric Administration (NOAA). As US federal agencies undergo institutional changes, we acknowledge that NCEI data findability and access may be impacted in the near‐future. Here we support the user community by documenting the existing data sets and their current access. Any questions/concerns about our solar and space weather data sets can be directed to ncei.info@noaa.gov.